Effects of feed additives in the diet of male dairy beef calves on physiological status and rumen microbial fermentation pre- and postweaning - E. Romera-Recio; E. Ramos-Morales; A. Belanche; M. Hassan; P. Romero; A. Gómez; I. Rivelli; N. Llanes; J. Torra; D.R. Yáñez-Ruiz (Animal Feed Science and Technology, 2025)

Risks, resources, and refugia: Spatial overlap between yellow-eyed penguin foraging distribution and prey, commercial fisheries, and marine protected areas - Rachel P. Hickcox; Thomas Mattern; Melanie J. Young; Mariano Rodríguez-Recio; Yolanda van Heezik; Philip J. Seddon (Biological Conservation, 2023)

Highly efficient Cu2O@CuxFeyO4 nanohybrid catalyst for the degradation of emerging pollutants - S. Fernández-Velayos; F.J. Recio; F.J. Palomares; N. Menéndez; P. Herrasti; E. Mazarío (Journal of Water Process Engineering, 2023)

Staying close to home: Marine habitat selection by foraging yellow-eyed penguins using spatial distribution models - Rachel P. Hickcox; Thomas Mattern; Mariano Rodríguez-Recio; Melanie J. Young; Yolanda van Heezik; Philip J. Seddon (Frontiers in Marine Science, 2022)
Endangered yellow-eyed penguins ( Megadyptes antipodes ) are central-place, benthic-diving foragers that search for prey in the productive marine areas off the coast of the South Island, New Zealand. Like other seabirds, they target specific, reliable areas of high prey abundance, which are often associated with oceanographic characteristics such as bathymetry, seafloor sediment type, and sea surface temperature. Employing GPS tracking data collected between 2003 and 2021, we created species distribution models using maximum entropy modelling (Maxent) to determine foraging space use and habitat suitability for yellow-eyed penguins across their entire South Island range and within five distinct subpopulations: Banks Peninsula, North Otago, Otago Peninsula, the Catlins, and Stewart Island. We quantified the importance of environmental variables for predicting foraging site selection during and outside the breeding season. Significant regional variation existed in predicted probability of penguin presence, and proximity to the nearest breeding area was a key predictor of suitable foraging habitat. When distance was not included in the models, dissolved oxygen concentration was the most important predictor in the overall South Island model and the North Otago, Otago Peninsula, and the Catlins subpopulation models, whereas water current speed and mean monthly turbidity were most important in Banks Peninsula and Stewart Island subpopulation models, respectively. Dynamic variables related to prey availability were often the most important variables in model predictions of the habitat selection of yellow-eyed penguins. Visualisations and findings from this study, particularly of the observed interactions between penguins and their marine habitat, can be used to direct conservation and resources during marine spatial planning and species management.

The Faja Eruptiva of the Eastern Puna and the Sierra de Calalaste, NW Argentina: U–Pb zircon chronology of the early Famatinan orogeny - C. Casquet; P. Alasino; C. Galindo; R. Pankhurst; J. Dahlquist; E. G. Baldo; C. Ramacciotti; S. Verdecchia; M. Larrovere; C. W. Rapela; C. Recio (Journal of Iberian Geology, 2021)

Identification of compound causing yellow bone discoloration following alpha-glycosyl isoquercitrin exposure in Sprague–Dawley rats - Jeffrey P. Davis; Mihoko Koyanagi; Robert R. Maronpot; Leslie Recio; Shim-mo Hayashi (Archives of Toxicology, 2020)
Previous rat toxicity studies of alpha -glycosyl isoquercitrin (AGIQ), a water-soluble flavonol glycoside derived from rutin, revealed systemic yellow bone discoloration. This investigative study was conducted to determine the AGIQ metabolite(s) responsible for the discoloration. Female Sprague–Dawley rats were administered dietary AGIQ at doses of 0%, 1.5%, 3.0%, or 5.0% (0, 1735.0, 3480.8, and 5873.7 mg/kg/day, respectively) for 14 days, followed by a 14- or 28-day recovery period. Measurements of quercetin in urine and quercetin, quercetin 3-O-glucuronide, kaempferol, and 3-o-methylquercetin metabolites of AGIQ in bone (femur), white and brown fat, and cerebrum samples were conducted following the exposure period and each recovery period. Gross examination of the femur revealed yellow discoloration that increased in intensity with dose and was still present in a dose-related manner following both recovery periods. Quercetin, at levels correlating with AGIQ dose, was measured in the urine following the 14-day exposure period and, at lower concentrations, 14 or 28 days following cessation of AGIQ exposure. All four metabolites were present in a dose-dependent manner in the femur following 14 days of dietary exposure; only quercetin, quercetin 3-O-glucuronide, and 3-o-methylquercetin were present during the recovery periods. Quercetin, quercetin 3-O-glucuronide, and 3-o-methylquercetin were detected in white fat (along with kaempferol), brown fat (excluding quercetin due to analytical interference), and cerebrum samples, indicating systemic availability of the metabolites. Collectively, these data implicate quercetin, quercetin 3-O-glucuronide, or 3-o-methylquercetin (or a combination thereof) as the most likely metabolite of AGIQ causing the yellow discoloration of bone in rats administered dietary AGIQ.

Can dynamic in vitro digestion systems mimic the physiological reality? - D. Dupont; M. Alric; S. Blanquet-Diot; G. Bornhorst; C. Cueva; A. Deglaire; S. Denis; M. Ferrua; R. Havenaar; J. Lelieveld; A. R. Mackie; M. Marzorati; et al. (Critical Reviews in Food Science and Nutrition, 2019)

Seasonal and latitudinal variation in seagrass mechanical traits across Europe: The influence of local nutrient status and morphometric plasticity - L. M. Soissons; M. M. van Katwijk; G. Peralta; F. G. Brun; P. G. Cardoso; T. F. Grilo; B. Ondiviela; M. Recio; M. Valle; J. M. Garmendia; F. Ganthy; I. Auby; et al. (Limnology and Oceanography, 2018)
Seagrasses are marine flowering plants distributed worldwide. They are however threatened, mostly due to the increase of human activities. Seagrasses have the capacity to adapt their morphological, physiological, and mechanical traits to their local conditions. Mechanical traits have been identified as a good tool to investigate a plant‐species capacity to withstand physical forces or disturbances but are still sparsely studied in seagrasses. With this study, we aimed to assess how the mechanical traits of a broadly spread seagrass species vary along a latitudinal gradient in relation to its morphometric plasticity and nutrient status. We found that seagrasses acclimate their mechanical traits in relation to their physiological or morphological traits, both over the growing season and across a latitudinal range: leaves were weaker and thinner in northern areas, particularly at the end of the growing season. Besides the influence of the latitudinal gradient, leaf mechanical strength and stiffness were both strongly affected by their morphometric plasticity. Moreover, we showed that leaves mechanical traits change depending on their nutrient status: leaves were stronger and stiffer in oligotrophic conditions as compared to more eutrophic conditions. Thus, our results imply that, under eutrophication, leaves become weaker and thus more vulnerable to physical forces. This vulnerability is higher in the north at the end of the growing season. The latter is consistent with the more ephemeral character of northern seagrass meadows, in contrast to the more evergreen southern meadows.

Pollen limitation may be a common Allee effect in marine hydrophilous plants: implications for decline and recovery in seagrasses - B. I. Van Tussenbroek; L. M. Soissons; T. J. Bouma; R. Asmus; I. Auby; F. G. Brun; P. G. Cardoso; N. Desroy; J. Fournier; F. Ganthy; J. M. Garmendia; L. Godet; et al. (Oecologia, 2016)

Adsorption of chromium(VI) onto electrochemically obtained magnetite nanoparticles - L. J. Martínez; A. Muñoz-Bonilla; E. Mazario; F. J. Recio; F. J. Palomares; P. Herrasti (International Journal of Environmental Science and Technology, 2015)

MiR-205 is downregulated in hereditary hemorrhagic telangiectasia and impairs TGF-beta signaling pathways in endothelial cells - Sebastien P. Tabruyn; Sylvain Hansen; Maria-Luisa Ojeda-Fernández; Nicolas Bovy; Roberto Zarrabeitia; Lucia Recio-Poveda; Carmelo Bernabéu; Joseph A. Martial; Luisa-Maria Botella; Ingrid Struman (Angiogenesis, 2013)

Analysis of parcel-based image classification methods for monitoring the activities of the Land Bank of Galicia (Spain) - T. Hermosilla; J. M. Díaz-Manso; L. A. Ruiz; J. A. Recio; A. Fernández-Sarría; P. Ferradáns-Nogueira (Applied Geomatics, 2012)

Trends in grass pollen season in southern Spain - Herminia García-Mozo; C. Galán; P. Alcázar; C. Díaz de la Guardia; D. Nieto-Lugilde; M. Recio; P. Hidalgo; F. Gónzalez-Minero; L. Ruiz; E. Domínguez-Vilches (Aerobiologia, 2010)

Geochronological, stable isotopes and fluid inclusion constraints for a premetamorphic development of the intrusive-hosted Björkdal Au deposit, northern Sweden - K. Billström; C. Broman; E. Jonsson; C. Recio; A. J. Boyce; P. Torssander (International Journal of Earth Sciences, 2009)

Identification and relationships of accessions grown in the grapevine (Vitis vinifera L.) Germplasm Bank of Castilla y Léon (Spain) and the varieties authorized in the VQPRD areas of the region by SSR-marker analysis - J. C. Santana; E. Hidalgo; A. I. de Lucas; P. Recio; J. M. Ortiz; J. P. Martín; J. Yuste; C. Arranz; J. A. Rubio (Genetic Resources and Crop Evolution, 2008)